Lost Bodies : Inhabiting the Borders of Life and Death - Tanner, Laura E., 1961- (Book collections on Project MUSE., 2006)
"If the dying body makes us flinch and look away, struggling not to see what we have seen, the lost body disappears from cultural view, buried along with the sensory traces of its corporeal presence."--The IntroductionAmerican popular culture conducts a passionate love affair with the healthy, fit, preferably beautiful body, and in recent years theories of embodiment have assumed importance in various scholarly disciplines. But what of the dying or dead body? Why do we avert our gaze, speak of it only as absence? This thoughtful and beautifully written book-illustrated with photographs by Shellburne Thurber and other remarkable images-finds a place for the dying and lost body in the material, intellectual, and imaginary spaces of contemporary American culture. Laura E. Tanner focuses her keen attention on photographs of AIDS patients and abandoned living spaces; newspaper accounts of September 11; literary works by Don DeLillo, Donald Hall, Sharon Olds, Marilynne Robinson, and others; and material objects, including the AIDS Quilt. She analyzes the way in which these representations of the body reflect current cultural assumptions, revealing how Americans read, imagine, and view the dynamics of illness and loss. The disavowal of bodily dimensions of death and grief, she asserts, deepens rather than mitigates the isolation of the dying and the bereaved. Lost Bodies will speak to anyone imperiled by the threat of loss